The Diversity of Ray-finned Fishes (Actinopterygii) in Plio-Pleistocene Java - Donan Satria Yudha; Muhammad Ageng Prabowo; Rusyad Adi Suriyanto; Didit Hadi Barianto (Universitas Gadjah Mada, 2020)
Java has been known in the world of Paleontology as a contributor to the findings of Homo erectus fossils, but there are still other fossil findings that have not been identified until now, especially fossil fishes of the subclass Actinopterygii. This research was conducted to recognize the diversity of the actinopterygians fishes in Plio-Pleistocene of Java and to determine the diagnostic characters of each taxon group of fossils in the Plio-Pleistocene of Java. The study was carried out using comparative anatomical methods with present-day specimens and fossil findings collection of the Laboratory of Bioanthropology and Paleoanthropology, Faculty of Medicine, Public Health and Nursing, Universitas Gadjah Mada; Bandung Geological Museum and Sangiran Early Man Site. The research found at least 8 species of fish fossils in Java which belong to three order, i.e., the order Siluriformes with 5 identified species: Bagarius gigas, Hemibragus nemurus, Clarias macrocephalus, family Ariidae with indeterminate genus or species, Plotosus canius, Clarias batrachus, and family Pangasiidae with indeterminate genus or species; the order Perciformes with two identified species: Anabas testudineus and Sphyraena crassidens; and the order Cypriniformes with one identified species: Osteochilus vittatus. Based on the fossil findings showed that the Java Island during the Plio-Pleistocene used to be a marine environment that gradually ascending into a lowland river which closes to mangrove swamps and estuaries while the ancient Bandung lake site was a lacustrine environment with calm currents and is overgrown with riparian vegetation.